Analysis of Factors Affecting the Profitability of Logistics Companies During the Covid-19 Pandemic - Sri Liniarti; Rizky Surya Andhayani Nasution (Institute of Computer Science (IOCS), 2022)
This research aims to determine the effect of Net Profit Margin (NPM), and Operating Expenses to Operating Income (BOPO) to Return On Assets (ROA). The type of research used is Explanatory Research, with a quantitative approach. Sampling technique with purposive sampling with company criteria logistics that presents financial statements for the period 20 19 to 20 20 so that a sample of 7 . is obtained companies and 14 data samples. The analysis used is multiple linear regression analysis. The results of this study are known that simultaneously and partially NPM and BOPO have a significant effect on ROA.